2021
DOI: 10.1155/2021/7092143
|View full text |Cite
|
Sign up to set email alerts
|

Fracability Evaluation Method and Influencing Factors of the Tight Sandstone Reservoir

Abstract: Fracability evaluation is the basis of reservoir fracturing and fracturing zone optimization. The tight sandstone reservoir is characterized by low porosity and low permeability, which requires hydraulic fracturing to improve industrial productivity. In this study, a systematic model was proposed for the fracability evaluation of tight sandstone reservoirs. The rock mechanics tests and sonic tests demonstrated that tight sandstone reservoir is characterized by high brittleness, high fracture toughness, and wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Fractal theory can quantitatively describe the complexity and heterogeneity of pore structure [9,10,[19][20][21][22][23]. The fractal dimension of the Chang 6 3 sublayer was calculated in this study, the results indicated that the larger fractal dimension, the more complex of porethroat structure, which was consistent with previous researches [24][25][26][27][28].…”
Section: The Parameters Ofsupporting
confidence: 88%
See 1 more Smart Citation
“…Fractal theory can quantitatively describe the complexity and heterogeneity of pore structure [9,10,[19][20][21][22][23]. The fractal dimension of the Chang 6 3 sublayer was calculated in this study, the results indicated that the larger fractal dimension, the more complex of porethroat structure, which was consistent with previous researches [24][25][26][27][28].…”
Section: The Parameters Ofsupporting
confidence: 88%
“…Experimental methods are conducted to evaluate the pore-throat structure, such as image observation methods represented by scanning electron microscopy (SEM) and casting thin sections (CTS), photoelectromagnetic radiation methods by nuclear magnetic resonance (NMR) and CT scanning, and fluid injection method by N 2 gas adsorption measurements and high-pressure mercury injection (HPMI) as well as constant-rate mercury injection (CRMI) [9][10][11][12][13][14][15][16]. Considering the complex pore-throat characteristics and strong heterogeneity caused by complicated deposition and diagenesis processes, it is hard to identify the microporethroat structure of tight sandstone reservoirs by a single method [5,[17][18][19][20][21][22][23][24][25][26]. For instance, although the image observation methods (SEM and CTS) can directly observe the geometry and the size of the pore-throat within sight, its visual field is too narrow to represent the whole sample [27].…”
Section: Introductionmentioning
confidence: 99%